Apport de la micro-usure dentaire à la reconstitution du régime alimentaire des anciens Pascuans - Caroline Polet; Céline Bourdon; Martine Vercauteren; Jean-Louis Slachmuylder (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
This study concerns the analysis of the dental microwear of 71 Easter Islanders who lived between the 13th and the 20th centuries and whose skeletons are housed in the Sebastian Englert Museum (Easter Island) as well as the Royal Institute of Natural Sciences of Belgium.The vestibular surface of the first and second permanent molars was examined by electron scanning microscope, at an enlargement of 178 times. The number of micro-striations, their length and their orientation were recorded in a circular area of 300 μm diameter using the Microware 4.02 program of P. Ungar.The pattern of microwear of the Easter Islanders indicates consumption of food which was not very abrasive, mainly of plant origin, which can be attributed to the important place held by sweet potatoes in their daily diet. A comparison with other populations previously studied (medieval and Neolithic populations in Belgium) indicates that the pattern of dental microwear of the Easter Islanders presents the most similarities with that of the Cistercians of the abbey of Dunes de Coxyde who consumed marine fish. Differences according to sex and age at death were not observed. Our study shows nevertheless that the so-called “royal” clan is distinguished from the other clans by its dental microwear. More consumption of products of animal origin by the socially privileged group could be the reason for this distinction.